2018
DOI: 10.1002/gps.4961
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of gesture‐verbal treatment and doll therapy for managing neuropsychiatric symptoms in older patients with dementia

Abstract: Background The prevalence of neuropsychiatric symptoms (NPS) diminishes the quality of life and increases the care burden in patients with dementia. Despite the clinical importance of dementia‐associated NPS, no protocols for treating NPS are already well established. Attention has turned to the effectiveness of nonpharmacological treatments for NPS since their potential safe alternative to pharmacotherapy. Objective This study is aimed to compare the effects in older individuals with dementia living in a resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 57 publications
(105 reference statements)
1
20
0
1
Order By: Relevance
“…Another study that compared the effectiveness of doll therapy and gesture-verbal therapy in managing the neuropsychiatric symptoms of patients with dementia found that doll therapy was more effective in managing agitation. 44 The same study found that, compared to the control group, the doll therapy intervention group displayed decreased levels of agitation, irritability, apathy, depression, and delusion. 44 In literature on the subject, the effects of doll therapy on patients with dementia have been attributed to attachment theory, 11,22 in which protection and safety are important for the individual, and the need for attachment may arise with the occurrence of insecurity or disease.…”
Section: Effect Of Doll Therapy On the Agitation And Behavioral Status Of Individualsmentioning
confidence: 92%
See 1 more Smart Citation
“…Another study that compared the effectiveness of doll therapy and gesture-verbal therapy in managing the neuropsychiatric symptoms of patients with dementia found that doll therapy was more effective in managing agitation. 44 The same study found that, compared to the control group, the doll therapy intervention group displayed decreased levels of agitation, irritability, apathy, depression, and delusion. 44 In literature on the subject, the effects of doll therapy on patients with dementia have been attributed to attachment theory, 11,22 in which protection and safety are important for the individual, and the need for attachment may arise with the occurrence of insecurity or disease.…”
Section: Effect Of Doll Therapy On the Agitation And Behavioral Status Of Individualsmentioning
confidence: 92%
“…44 The same study found that, compared to the control group, the doll therapy intervention group displayed decreased levels of agitation, irritability, apathy, depression, and delusion. 44 In literature on the subject, the effects of doll therapy on patients with dementia have been attributed to attachment theory, 11,22 in which protection and safety are important for the individual, and the need for attachment may arise with the occurrence of insecurity or disease. 21,22 Accordingly, it is suggested that behavioral disturbances and agitation in patients with dementia demonstrate a craving for attachment, which is a psychological need.…”
Section: Effect Of Doll Therapy On the Agitation And Behavioral Status Of Individualsmentioning
confidence: 92%
“…The lack of solid scienti c evidences is mainly due to the di cult in standardization of nonpharmacologic intervention; as regards DT some attempt towards standardization have been done with well-designed randomized controlled clinical trials [20,[47][48][49]. The randomized-controlled clinical trials agree on the e cacy of DT in ameliorating BPSD in nursing home residents.…”
Section: Discussionmentioning
confidence: 99%
“…Some nondrug therapies, such as reminiscence therapy, music therapy, aromatherapy, and doll therapy (DT), have been shown to be effective in temporarily relieving or improving symptoms and enhancing the quality of life. Among them, DT has been widely investigated due to its simplicity and costeffectiveness (8)(9)(10)(11). Here, we review the studies related to the treatment of AD with DT, with an attempt to better understand the effectiveness and clinical applications of this nondrug therapy.…”
Section: Overviewmentioning
confidence: 99%
“…Cai et al performed a controlled trial in 186 AD patients and found 93 patients in the DT group showed significantly improved language, place judgment, memory, movement, and cognitive function compared to 93 patients in the control group (treated with conventional therapy). Balzotti et al (11) applied DT in 10 AD patients, and the DT group showed significant improvements in agitation, irritability, and other psychological symptoms relative to controls; the patients' interaction and familiarity with the dolls facilitated the formation of communication and attachment relationships, reduced behavioral and emotional disturbances, delayed the progression of the disease to a certain extent, and improved the cognitive function of patients.…”
Section: Improving Cognitive Function and Memorymentioning
confidence: 99%